THE INFLUENCE OF COUNTRY OF ORIGIN ON PURCHASE DECISIONS THROUGH PRICE AS A MEDIATING VARIABLE IN XIAOMI PRODUCTS - Nurul Fadilah Aswar (Adisam Publisher, 2025)
This study aims to analyze the influence of Country of Origin (COO) on Price and Purchase Decisions, both directly and indirectly, with Price as a mediating variable, focusing on Xiaomi products. The findings reveal that consumer perceptions of a product's country of origin significantly influence their evaluation of price. However, perceptions of the country of origin do not directly impact purchase decisions, as consumers prioritize product quality and features. Price emerges as the primary determinant of purchase decisions, with competitive pricing aligned with quality driving consumer purchases. Additionally, perceptions of the country of origin indirectly influence purchase decisions through price. This research provides strategic insights for Xiaomi to manage brand image, optimize pricing strategies, and enhance competitiveness in the global market.